2018
DOI: 10.1002/cne.24471
|View full text |Cite
|
Sign up to set email alerts
|

c‐Fos marking of identified midbrain neurons coactive after nicotine administration in‐vivo

Abstract: Despite the reduced life expectancy and staggering financial burden of medical treatment associated with tobacco smoking, the molecular, cellular, and ensemble adaptations associated with chronic nicotine consumption remain poorly understood. Complex circuitry interconnecting dopaminergic and cholinergic regions of the midbrain and mesopontine tegmentum are critical for nicotine associated reward. Yet our knowledge of the nicotine activation of these regions is incomplete, in part due to their cell type divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Whereas cFos expression reflects a snapshot of neuronal activity ~30-60 minutes prior to the time of sacrifice 55 while the animals are actively being exposed to the vapor. The cFos increase following acute and decrease following chronic nicotine vapor exposure is consistent with previous studies examining the patterns of activity following systemic nicotine exposure 51 .…”
Section: Discussionsupporting
confidence: 90%
“…Whereas cFos expression reflects a snapshot of neuronal activity ~30-60 minutes prior to the time of sacrifice 55 while the animals are actively being exposed to the vapor. The cFos increase following acute and decrease following chronic nicotine vapor exposure is consistent with previous studies examining the patterns of activity following systemic nicotine exposure 51 .…”
Section: Discussionsupporting
confidence: 90%
“…The VTA and its dopaminergic activity is thought to underlie reward signaling in the brain and is a major target of drugs of abuse, including nicotine [ 24 ]. Nicotine has previously been shown to increase cell firing [ 25 , 26 ] and cFos expression [ 27 ] in the VTA. Additionally, studies have found that both rats [ 8 ] and mice [ 7 ] will self-administer nicotine vapor.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting with mouse anti-tyrosine hydroxylase (TH) antibody confirmed that it specifically recognizes a 55–60 kDa protein in ventral tegmental area lysates (manufacturer's datasheet; Gumbs et al 2019 ). Sheep anti-TH antibody was previously characterised by Baur et al ( 2018 ). Western blot of rat brain corpus striatum homogenates show a single band of ∼62 kDa (manufacturer's datasheet; Haycock and Haycock 1991 ; Kansy et al 2004 ).…”
Section: Methodsmentioning
confidence: 99%